Precarity, Hospitality, and the Becoming of a Subject That Matters: A Study of Syrian Refugees in Lebanese Tented Settlements - Hultin, Lotta; Introna, Lucas D.; Göransson, Markus Balázs; Mähring, Magnus (Organization studies, 2022)
How is it possible to gain a sense that you have a voice and that your life matters when you have lost everything and live your life as a ‘displaced person’ in extreme precarity? We explore this question by examining the mundane everyday organizing practices of Syrian refugees living in tented settlements in Lebanon. Contrasting traditional empirical settings within organization studies where an already placed and mattering subject can be assumed, our context provides an opportunity to reveal how relations of recognition and mattering become constituted, and how subjects in precarious settings become enacted as such. Specifically, drawing on theories on the relational enactment of self and other, we show how material-discursive boundary-making and invitational practices – organizing a home, cooking and eating, and organizing a digital ‘home’ – function to enact relational host/guest subject positions. We also disclose how these guest/host relationalities create the conditions of possibility for the enactment of a subject that matters, and for the despair enacted in everyday precarious life to transform into ‘undefeated despair’.